Impact of neoadjuvant chemotherapy and stereotactic body radiation therapy (SBRT) on R0 resection rate for borderline resectable and locally advanced pancreatic cancer. Issue 7 (July 2021) - Zakem, Sara J.; Mueller, Adam C.; Meguid, Cheryl; Torphy, Robert J.; Holt, Douglas E.; Schefter, Tracey; Messersmith, Wells A.; McCarter, Martin D.; Del Chiaro, Marco; Schulick, Richard D.; Goodman, Karyn A.
Abstract: Background: The role of neoadjuvant stereotactic body radiation therapy (SBRT) in patients with borderline resectable pancreas cancer (BRPC) and locally advanced pancreas cancer (LAPC) remains controversial. Methods: We retrospectively evaluated BRPC and LAPC patients treated at our institution who underwent 2–3 months of chemotherapy followed by SBRT to a dose of 30–33 Gy. Overall survival (OS) and recurrence-free survival (RFS) were estimated and compared by Kaplan–Meier and log-rank methods. Results: We identified 103 (85 BRPC and 18 LAPC) patients treated per our neoadjuvant paradigm between 2011 and 2018, with resectability based on NCCN definitions. Median follow up was 25 months. Of patients completing neoadjuvant therapy, 73 (71%) underwent definitive resection. Seventy-one (97%) patients with definitively resected tumors had R0 resection and 5 (7%) had a complete pathologic response CR to neoadjuvant therapy. The median overall survival (OS) of the cohort was 24 months. Those with a complete or marked pathologic response had significantly better OS than those with a moderate response (41 vs 24 months, p < 0.02) and patients unable to undergo definitive surgery (17 months, p < 0.0003). Six resected patients experienced grade ≥3 surgical complications. Conclusions: Neoadjuvant chemotherapy and SBRT are associated with promising pathologic response rates and R0 resection rates, with acceptable perioperative morbidity.